Factors that influence agent’s awareness towards money laundering in Etiqa Takaful Berhad Temerloh Branch / Mohd Nor Saiful Ghazali - Ghazali, Mohd Nor Saiful (Faculty of Business and Management, 2010)
This research aims to investigate the factors that influence agent’s awareness towards money laundering in Etiqa Takaful Berhad Temerloh Branch. According to the statistic by Bank Negara Malaysia (BNM), 94 money laundering cases involving proceeds amounting RM 1.2 billion occur as at August 2010. Educational level, years of service and mass media are the independent variables. The dependent variable is the level of awareness. The objectives of this study are, firstly, to investigate the level of agent’s awareness towards money laundering; secondly, to determine whether there is relationship between education level, years of service and mass media with the agent’s awareness towards money laundering; and thirdly, to identify the most contributing factor that influences agent’s awareness towards money laundering. In this study, researcher has use exploratory, descriptive and causal research as research design. The data collection method used is only primary data, it is questionnaire. Questionnaires were distributed to 50 agents who employed in Etiqa Takaful Berhad Temerloh Branch. Then, both probability and non-probability sampling are use as sampling method. Besides, three hypotheses were developed and tested using Pearson Chi Square assisted by Statistical Package for Social Science (SPSS) Version 16.0. The findings indicate the agents are aware towards money laundering. Between the three variables, years of service and mass media has no significant relationship with agent’s awareness. So, there are only education level shows the significant relationship and it become the most contributing factor that influence agent’s awareness.